Construction of nitrogen and phosphorus flux of land-based pond mariculture: Taking the Xiangshan Bay as an example - Yiwei Du; Xiaoguang Li; Siru Liu; Tian Lin (HydroResearch)
The construction of nutrient flux can provide a scientific basis for understanding the fate in the aquaculture systems to facilitate sustainable coastal environment management. In this study, the tailwater of the mariculture pond from 65 sampling points in the Xiangshan Bay were measured. The average concentrations of total nitrogen and total phosphorus of the samples were 2.16 mg/L and 0.11 mg/L, which were lower than Category I of Mariculture Tailwater Discharge Standards of Zhejiang Province. Two methods were applied to estimate the discharge flux of the total nitrogen and total phosphorus from mariculture ponds in the Xiangshan Bay. The application of chemical analysis method was technically optimized by means of area data obtained by high-density sampling campaign and GIS method. It was estimated that the annual discharge flux of total nitrogen and total phosphorus via chemical analysis method were 271.2–338.9 tones and 7.6–9.5 tones, respectively. Potential environmental effects were further assessed according to monthly discharge flux combined with seasonal variations of hydrodynamic environment. In comparison, the estimated annual fluxes of chemical analysis method were much lower than the ones of pollution discharging coefficient method which were 357.56 tones/year and 22.00 tones/year, respectively. It is considered that part of nitrogen and phosphorus nutrients deposited into the bottom sediment of the ponds or coastal environment. The continuous loading of nitrogen and phosphorus nutrients into sediment can increase the risk of secondary release, especially in such semi-enclosed bay.